Hall effects on MHD flow past an accelerated plate with heat transfer - Sundarnath, Kavin J.; Muthucumaraswamy, Rajamanickam (Zielona Góra: Uniwersytet Zielonogórski)
Hall current and rotation on an MHD flow past an accelerated horizontal plate relative to a rotating fluid, in the presence of heat transfer has been analyzed. The effects of the Hall parameter, Hartmann number, rotation parameter (non-dimensional angular velocity), Grashof?s number and Prandtl number on axial and transverse velocity profiles are presented graphically. It is found that with the increase in the Hartmann number, the axial and transverse velocity components increase in a direction opposite to that of obtained by increasing the Hall parameter and rotation parameter.
Keywords: Hall parameter; Hartmann number; heat transfer; Grashof`s number; Prandtl number